2011
DOI: 10.1371/journal.pone.0020955
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation-Induced Aggression Potentiates Anxiety and Depressive-Like Behavior in Male Mice Subjected to Unpredictable Chronic Mild Stress

Abstract: BackgroundAccumulating epidemiological evidence shows that life event stressors are major vulnerability factors for psychiatric diseases such as major depression. It is also well known that social isolation in male mice results in aggressive behavior. However, it is not known how social isolation-induced aggression affects anxiety and depressive-like behavior in isolated male mice subjected to unpredictable chronic mild stress (CMS), an animal model of depression.Methodology/Principal FindingsC57/B6 male mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 55 publications
1
77
1
Order By: Relevance
“…Second, because mice were housed five per cage, maintaining animals in separate cages may have caused social isolation stress. Matsumoto et al (2005) showed that isolation stress induces aggression in mice, and Ma et al (2011) reported that this type of gained aggression potentiates depressive-like behavior and anxiety. Increased anxiety might have caused the reduction of the intake of saccharin.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because mice were housed five per cage, maintaining animals in separate cages may have caused social isolation stress. Matsumoto et al (2005) showed that isolation stress induces aggression in mice, and Ma et al (2011) reported that this type of gained aggression potentiates depressive-like behavior and anxiety. Increased anxiety might have caused the reduction of the intake of saccharin.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal models of chronic stress, including social defeat (Rygula et al, 2005), restraint stress (Strekalova et al, 2004;Wood et al, 2008) and CUS (Kompagne et al, 2008;Bessa et al, 2009), exhibit behavioral endophenotypes of major depression including behavioral despair, anhedonia and social avoidance ( Figure 1D). Further, animals subjected to social isolation or CUS also exhibit enhanced anxiety (Koike et al, 2009;Ma et al, 2011) (Figure 1D), and potentiated fear and startle behavior (McGuire et al, 2010). While exposure to a variety of chronic or acute severe stressors evokes depressive and anxiogenic behavioral phenotypes, it is important to note that the nature and intensity of behavioral effects are dependent on both the specific stressor paradigm (Table 1), and the genetic background and epigenetic landscape of the animal (Chaudhury et al, 2014;O'Leary et al, 2014).…”
Section: Chronic Stress and Anxiety Depressive And Social Behaviormentioning
confidence: 99%
“…Acute restraint or tail shock stress enhances hippocampal CA1 neuron spinogenesis in males ) ( Figure 2B). While it is unclear if acute stress-mediated spinogenesis exerts an adaptive Watanabe et al, 1992;Luine et al, 1994;Magarinos et al, 1997;Pavlides et al, 2002;Strekalova et al, 2004;Pawlak et al, 2005;Atif et al, 2008;Wood et al, 2008;Veena et al, 2009;Christian et al, 2011;Liu et al, 2012;Hillerer et al, 2013 CUS ( -Behrens et al, 1994;Sousa et al, 2000;Lee et al, 2006;Holderbach et al, 2007;Kompagne et al, 2008;Bessa et al, 2009;de Vasconcellos-Bittencourt et al, 2011;Gong et al, 2011;Ma et al, 2011 Social stressors (social defeat, severe fatal social stressor) Decreased dendritic complexity, decreased CA3 neuron dendritic length. Depl...…”
Section: Adaptive Effects Of Adult Mild Stress Exposure On the Hippocmentioning
confidence: 99%
“…After over all test, mice were replaced in to their home cages and returned to breeding room. The FST and TST in mice are the most widely used behavioral assays for detecting potential antidepressant-like activity (Cryan and Holmes, 2005;Ma et al, 2011Ma et al, , 2013Ma et al, , 2014Zhang et al, 2015).…”
Section: Behavioral Testsmentioning
confidence: 99%